Revision of Orthophytum (Bromeliaceae): the species with sessile inflorescences - Louzada, R. B.; Wanderley, M. D. L. (Phytotaxa, 2010)
Orthophytum is a bromeliad genus restricted to Brazil with records for the states of Paraiba, Pernambuco, Alagoas, Sergipe, Bahia, Espirito Santo and Minas Gerais. The genus is usually divided in two informal groups based on the presence or absence of a peduncle. This paper presents a taxonomic revision of the 12 species in the group with sessile inflorescences and descriptions of the genus and species, nomenclatural and ecological notes, as well as illustrations are provided. The new species Orthophytum ulei is described. The conservation status for each species is evaluated using the World Conservation Union (IUCN) criteria.